Therapies and therapeutic approaches in congenital disorders of glycosylation - Thiel, Christian; Körner, Christian (Glycoconjugate journal, 2013)
Inborn errors in glycoconjugate biosynthesis termed ‘Congenital Disorders of Glycosylation’ (CDG) comprise a rapidly expanding group of metabolic diseases in man. Up till now more than 60 different inherited disorders in N- and O-glycosylation pathways have been identified. They affect the biosynthesis of glycan moieties linked to proteins as well as lipids. Due to failures in protein glycosylation, CDG patients suffer from multi systemic disorders, which mostly present with severe psychomotor and mental retardations, muscular impairment, ataxia, failure to thrive and developmental delay. Although improved biochemical and genetic investigations led to identification of a variety of new molecular defects in glycoconjugate biosynthesis, effective therapies for most types of the CDG are so far not available. Therefore, intensive investigations on treatment options for this group of diseases have been carried out in recent years.